Using 3‐dimensional ultrasound islice technology for the diagnosis of developmental dysplasia of the hip. (9th December 2019) - Geng, Chenchen; Xu, Hongtao; Zhan, Xinfeng; Li, Li; Song, Qian; Zhang, Lu; Ge, Ling
Abstract : Objectives: This study aimed to investigate the reliability of 3‐dimensional (3D) ultrasound in screening for developmental dysplasia of the hip (DDH) by comparing the results with those of 2‐dimensional (2D) ultrasound. Methods: One hundred five infants who were younger than 6 months were enrolled in this study. All of the infants underwent 2D and 3D ultrasound scanning for DDH by novices and experts, and the images were graded by a lead expert. The scanning time and image grades were analyzed by Student t tests ( P < .05). The consistency of the α angle measurement between the novices and experts was evaluated by the intraclass correlation coefficient (ICC). Results: The 105 infants included 34 boys and 71 girls. On 2D scanning, there was agreement between the experts about the correct diagnosis, whereas in the novice group, 41 infants had misdiagnoses. There were no misdiagnoses with 3D scanning in either group. In the novice group, the mean image grades ± SD were 4.2 ± 1.3 (2D ultrasound) and 8.1 ± 0.7 (3D ultrasound; P < .05). In the expert group, the mean image grades were 7.4 ± 1.0 (2D ultrasound) and 8.2 ± 1.0 (3D ultrasound; P < .05). There was no statistically significant difference between the groups in the grades for 3D ultrasound ( P = .83). The scanning time for 3D ultrasound was shorter than that for 2D ultrasound in both groups ( P < .05). In the novice group, the ICC of the α angle between the 2D and 3D ultrasound results was 0.34, and in the expert group, it was 0.92. The ICCs were 0.35 and 0.84, respectively when comparing 2D and 3D ultrasound results in the groups. Conclusions: Three‐dimensional ultrasound required less time and showed greater inter‐rater reliability than 2D ultrasound for detecting DDH.